1988
DOI: 10.1002/pd.1970080311
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 14 mosaicism leading to cytogenetic discrepancies in chorionic villi sampled at different times

Abstract: Short- and long-term cultures of chorionic villi obtained in the 11th week of pregnancy revealed trisomy 14. After induced abortion trisomy 14 mosaicism was established in fetal skin and umbilical cord tissue while a second long-term culture of chorionic villi exhibited a normal karyotype. The results of the pathological investigations are discussed with respect to the cytogenetic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Disregarding possible fortuitous explanations, such as a coincidental favourable distribution of a mosaic cell population or complete selection against a chromosomally aberrant cell-line intra-embryonic and tolerance for the same cell-line extraembryonic, an abnormality found in the direct preparation and in the long-term culture must be present in the fetus. This may be illustrated by the cases described by Hammer et al (1991) andWegner et al (1988), where a false-positive diagnosis was made because a trisomy, initially detected in the direct preparation and long-term culture, was not confirmed in a second procedure. In both instances the trisomy could be recovered from fetal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Disregarding possible fortuitous explanations, such as a coincidental favourable distribution of a mosaic cell population or complete selection against a chromosomally aberrant cell-line intra-embryonic and tolerance for the same cell-line extraembryonic, an abnormality found in the direct preparation and in the long-term culture must be present in the fetus. This may be illustrated by the cases described by Hammer et al (1991) andWegner et al (1988), where a false-positive diagnosis was made because a trisomy, initially detected in the direct preparation and long-term culture, was not confirmed in a second procedure. In both instances the trisomy could be recovered from fetal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For practical and economic reasons we have ceased the routine use of short-term preparations. Ledbetter et al, 1990;Breed et al, 1990;Leschot et al, 1989;Miny et al, 1989;Wright et al, 1989; Vejerslev and Mikkelsen, 1989), although the authors have indicated more diagnostic dilemmas in the use of villi as compared with amniotic fluid cells as the source for analysis.Laboratory problems known to be associated with prenatal diagnoses include failure of cell growth, chromosomal mosaicism and pseudomosaicism, and MCC. Furthermore, discordant cytogenetic results have been observed between the cytotrophoblast cells derived from the trophoectoderm for short-term preparation and the mesodermally derived villus core cells for cultures.…”
mentioning
confidence: 99%
“…Ambiguous or uncertain results present difficulties in counselling and frequently warrant additional invasive procedures, increasing the risk of complications and delaying the reporting of critical information.Many published CVS and AC comparisons are derived from multicentre investigations through which cytogenetic methods, materials, and definitions may be incomparable; e.g., the frequency of mosaicism diagnosed correlates with the number of cells counted and with harvest by the in situ technique or after subcultivation. Although two single-centre studies (Wright et al, 1989; Young et al, 1991) compared prenatal diagnoses by CVS and AC, the patient populations differed. We were interested in exploring the cytogenetic results obtained from randomized studies on CVS versus AC, and TA versus TC CVS in settings with identical obstetrical and cytogenetic methods, which was not achieved in previous studies.The purpose of this study, accordingly, was to evaluate results in comparable groups of women, with the same laboratory processing all samples, using identical definitions and cell counting.…”
mentioning
confidence: 99%
“…Trisomy 14, on the other hand, was more frequent in placenta and amniotic fluid than in fetal tissue if the heart sample is excluded from table 1. Once again, the controversy regarding the sampling site was documented by Wegner et al [10] when they reported mosaic trisomy 14 detected on short-and long-term cultures of a chorionic villi sample obtained at 11 weeks of pregnancy which could not be reproduced in a 14-week chorionic villi sample from the same fetus but which was confirmed in fetal skin and umbilical cord tissue. Although a nonrandom distribution of aneuploid cells between different extra-embryonic cell lineages has been suggested [2], further studies would be required to determine if the different proportions of trisomic cells observed within the neonatal tissues are due to selection for or against particular trisomic cells in specific tissues or due to uneven compartmentalization of aneuploid cells during blastocyst development.…”
Section: Discussionmentioning
confidence: 99%
“…FISH analysis identified a female fetus with no aneuploidy involving chromosomes 13, 18, 21, X, or Y. On chromosome analysis, 17 metaphase spreads were examined revealing a double autosomal mosaicism involving chromosomes 8 and 14 (47,XX,+8 [10]/ 47,XX,+14 [7]). No normal cells were identified.…”
Section: Case Reportmentioning
confidence: 99%